Antioxidation activity and organic components analysis of Cestus Parviflorus grown in Libya (Journal of Academic Research, 2024)
Phytochemical screening of Cestus Parviflorus plant ethanolic extract was carried out revealing presence of most bioactive phytochemicals, including alkaloids, carbohydrates, glycosides, saponins, phytosterols, phenols, tannins, flavonoids, proteins, terpenes and quinones. For more depth analysis, GC-MS analysis was performed. Wide diverse of chemical classes was found in the ethanolic extract of the plant, long chain hydrocarbons, different types of terpenes, flavonoids, nitrogen and oxygen contained heterocyclic compounds and fatty acids and their esters. Five fatty acids were the most abundant in the ethanolic extract with 11.72% peak area, the acids are; Oleic acid (Z)-9-Octadecenoic acid), trans-13-Octadecenoic acid, cis-13-Octadecenoic acid and cis-Vaccenic acid. Anti oxidation activity of the plant powder also investigated, IC50 value of C. parviflorus plant was 3.95 μg/ml, lower than standard reagent ascorbic acid with 13.49 μg/ml and indicates that, C. Parviflorus is a strong and promising natural antioxidation agent.